2002
DOI: 10.1053/jhep.2002.32969
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial oxidative stress and CD95 ligand: A dual mechanism for hepatocyte apoptosis in chronic alcoholism

Abstract: Apoptosis plays an important role in the progression of alcohol-induced liver disease to cirrhosis. Oxidative stress is an early event in the development of apoptosis. The major aim of this study was to study the conditions in which oxidative stress occurs in chronic alcoholism and its relationship with apoptosis of hepatocytes. We have found that oxidative stress is associated with chronic ethanol consumption in humans and in rats, in the former independently of the existence of alcohol-induced liver disease.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
94
1
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(101 citation statements)
references
References 36 publications
4
94
1
2
Order By: Relevance
“…Interestingly, despite the little changes between HFD and CD; the Fas/FasL expression was significantly induced by moderate alcohol consumption in the HFA group, which is in agreement with previous findings in which ethanol and its metabolite acetaldehyde can induce the Fas/FasL expression from both in vitro and in vivo (Minana, et al, 2002;McVicker et al, 2006;Zhou et al, 2001). Moreover, it has been demonstrated that the hepatic steatosis sensitizes the liver to more injury and inflammation via up-regulation of Fas expression .…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, despite the little changes between HFD and CD; the Fas/FasL expression was significantly induced by moderate alcohol consumption in the HFA group, which is in agreement with previous findings in which ethanol and its metabolite acetaldehyde can induce the Fas/FasL expression from both in vitro and in vivo (Minana, et al, 2002;McVicker et al, 2006;Zhou et al, 2001). Moreover, it has been demonstrated that the hepatic steatosis sensitizes the liver to more injury and inflammation via up-regulation of Fas expression .…”
Section: Discussionsupporting
confidence: 91%
“…Elevated NO and cGMP in alcoholic cirrhosis in patients with alcoholic liver disease. Studies have shown increased plasma and tissue levels of markers of lipid peroxidation [13][14][15][16] , and reduced hepatic and plasma antioxidant content [17][18][19][20] . In the liver, as in many other organs, NO…”
Section: Wwwwjgnetcommentioning
confidence: 99%
“…16 Fas activation is considered the cause of several liver diseases, including viral hepatitis, alcoholic liver disease, and hepatocellular carcinoma. [17][18][19] Fas is expressed in normal mouse and human hepatocytes, 16 and its activation by agonistic Fas antibodies leads to massive apoptosis with fulminant liver failure in mice. 20,21 Genetic studies on fas mutant mice have revealed hepatic hyperplasia, presumably caused by reduced hepatocyte apoptosis.…”
mentioning
confidence: 99%